2018
DOI: 10.1371/journal.pone.0192883
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of monocytic HLA-DR expression differs between bacterial etiologies during the course of bloodstream infection

Abstract: ObjectiveIn the pathogenesis of sepsis, activation of both pro- and anti-inflammatory responses are key components, but knowledge is lacking on the association between bacterial etiology and development of dysregulated responses with sustained immunosuppression. The aim of this study was to evaluate how the immunosupression marker HLA-DR on monocytes (mHLA-DR) is associated with bacterial etiology and markers of inflammation during the clinical trajectory of bloodstream infection (BSI).MethodsNinety-one adults… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 35 publications
3
23
0
Order By: Relevance
“…Patients with an E. coli infection had expression levels similar to those found in healthy volunteers [11]. However, the population was heterogeneous and the observed differences might therefore be explained by the large differences in disease severity between patients in the different pathogen categories [11]. In the current cohort of septic shock patients, we do not find differences in mHLA-DR expression kinetics between patients with Gram-positive, Gram-negative and negative cultures.…”
Section: Discussionsupporting
confidence: 54%
See 4 more Smart Citations
“…Patients with an E. coli infection had expression levels similar to those found in healthy volunteers [11]. However, the population was heterogeneous and the observed differences might therefore be explained by the large differences in disease severity between patients in the different pathogen categories [11]. In the current cohort of septic shock patients, we do not find differences in mHLA-DR expression kinetics between patients with Gram-positive, Gram-negative and negative cultures.…”
Section: Discussionsupporting
confidence: 54%
“…Previous work revealed that, in patients with bloodstream infections, those with S. pneumonia infections showed a swift increase in mHLA-DR expression over and p values were calculated using repeated measures two-way ANOVA on log-transformed data vs. reference trajectory A (time*group interaction term). ***p < 0.001 calculated with one-way ANOVA on log-transformed data with Dunnett's multiple comparison test compared to baseline time, whereas patients with a S. aureus infection displayed a delayed recovery [11]. Patients with an E. coli infection had expression levels similar to those found in healthy volunteers [11].…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations